2021
DOI: 10.1111/jjns.12423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nursing procedures on the hand skin temperature of female hospital nurses

Abstract: Aims Nurses’ hand temperature may affect patient comfort but has not been investigated. This study aimed to determine female hospital nurses' hand skin temperature and clarify the effects of measurement site, time, nursing procedures, and environment. Design An observational study. Methods The middle finger, thenar eminence, hypothenar eminence, and medial forearm skin temperature of 29 female hospital nurses was measured at four time points during a day shift and before and after nursing procedures (hand disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The ability to fine-tune air conditioning is associated with a lower cold sensitivity. Existing studies have shown positive correlations between room temperature and female nurses’ skin temperature and between skin temperature and perceived cold sensitivity ( Suzuki et al, 2021 ). Clothing is also used to regulate the body temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to fine-tune air conditioning is associated with a lower cold sensitivity. Existing studies have shown positive correlations between room temperature and female nurses’ skin temperature and between skin temperature and perceived cold sensitivity ( Suzuki et al, 2021 ). Clothing is also used to regulate the body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Hand washing and sanitization have been reported to reduce hand skin temperature ( Suzuki et al, 2021 ). Frequent hand washing and sanitization are required for infection prevention in nurses’ work environments.…”
Section: Introductionmentioning
confidence: 99%